Computer-Assisted Avatar-Based Treatment for Dysfunctional Beliefs in Depressive Inpatients: A Pilot Study - Kocur, Martin; Dechant, Martin; Wolff, Christian; Nothdurfter, Caroline; Wetter, Thomas C.; Rupprecht, Rainer; Shiban, Youssef (Frontiers in Psychiatry, 2021)
Dysfunctional cognitions are a crucial part of depression. Cognitive therapy aims to modify dysfunctional beliefs. Typically, dysfunctional beliefs are questioned, and patients are trained to think of alternative functional beliefs. We developed a computer-assisted, exposure-based adjunct for cognitive therapy (CET-DB) that aims to reduce dysfunctional beliefs and symptom severity. Besides, it aims to promote alternative functional beliefs. In a randomised controlled trial with 34 patients diagnosed with major depression currently undergoing inpatient treatment at the university psychiatric hospital in Regensburg, Germany, participants were randomly assigned to receive either treatment as usual (TAU) or computer-assisted exposure-based treatment for dysfunctional beliefs (CET-DB) in addition to TAU. In CET-DB participants are faced with a virtual agent expressing their personal dysfunctional beliefs. Participants are asked to contradict these and express alternative functional beliefs. Assessments of conviction of dysfunctional beliefs, functional beliefs and symptom severity were done shortly before the intervention (pretreatment), right after the intervention (posttreatment) and 14 days later (follow-up). The reduction in conviction of dysfunctional beliefs and symptom severity, and the increase in conviction of alternative functional beliefs at posttreatment and follow-up were significantly greater for the group receiving CET-DB. Our study provides an indication in favour of the effectiveness of CET-DB for depressive patients. It is a simple tool that could support classical cognitive therapy. Further studies at different centres, with larger sample sizes and varying therapeutic contexts are required to prove the effectiveness of our intervention.